Evaluation of Village Fund Management Process Based on Permendagri No. 20 of 2018 in Tumpaan Dua Village, Tumpaan District, South Minahasa Regency - WATULINGAS, Monica; ELIM, Inggriani; KINDANGEN, Wulan D. (Journal of Governance, Taxation and Auditing, 2023)
Good governance in a country is an unavoidable necessity. Law Number 6 of 2014 which is intended for villages, makes villages free to run village administration. The regulation of villages with separate laws shows the government's political will to make villages the basis of development. The village is given the authority to regulate and manage its own household affairs. In its implementation, village autonomy provides very broad authority for the village government in administering village government. The implementation of this given authority uses village finances. This study aims to determine the suitability of the village fund management process based on Permendagri Number 20 of 2018 at the planning, implementation, administration, reporting, accountability stages, especially village funds in 2021. The research method used is descriptive qualitative method, with data collection methods through documentation and interviews. The results of this study indicate that the village fund management process is not in accordance with Permendagri Number 20 of 2018, especially in the planning stage of village financial management, and the draft village regulation regarding the Village Revenue and Expenditure Budget (APBDes) which was agreed in March 2021, which should have been agreed  in October 2020. This is because the Covid-19 outbreak has resulted in a delay in the implementation of village meetings and village development planning meetings and at the accountability stage where the APBDes realization report has not been included on the Tumpaan Dua Village website.